Analysis of Translation Understanding from Verbal to Visual on Trigonometry Concept - Silfanus Jelatu; Valeria Suryani Kurnila (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
Constructing representations in the form of visualization can help students connect with problem situations and facilitate students' ability to communicate their understanding of the problem. This implies the ability to translate mathematical concepts. This research is a descriptive study that aims to describe the ability to translate trigonometric ideas from verbal forms to visual forms of students. This research was conducted at mathematics education of STKIP Santu Paulus Ruteng which involved 75 first-level students as a sample. The results of this study indicate that the students’ at the mathematics education department of STKIP Santu Paulus Ruteng, especially in the new semester, were mostly still capable of teaching the translation of trigonometric concepts from verbal to visual forms, some of which were at the PU level with a percentage of 35.2%. In the second level, 30.6% is in the PUSM, SU category, 17.6%, NU is 13.8% and SM is 2.8%. The results of this research can be used as references for high school teachers to find out their graduation profile in terms of translational skills and also input for lecturers to be able to adjust the lecture process based on the characteristics that have been produced